Possibilismo Geográfico – Um Estudo sobre a Tempestade Solar de Maio de 1967 | Geographic Possibilism – A Study of the May 1967 Solar Storm - P.C.C. Teixeira, Margarida (Political Observer | Revista Portuguesa de Ciência Política (Portuguese Journal of Political Science), 2025)
The relevance that Geography holds in Geopolitics is clear, and therefore, it is necessary to pay attention to the perspective adopted in the analysis of various situations. The case study used was the solar storm of May 1967, and it was first necessary to identify the appropriate analytical approach, rejecting determinism due to its limitations. The study adopted geographical possibilism, which highlights the role of human agency in adapting to and reshaping the constraints imposed by the natural environment. The event was contextualized within the Cold War period, with particular attention given to the role of the Strategic Air Command and the North American Air Defense Command in the moments leading up to the astronomical occurrence. Through qualitative, bibliographical, and documentary research, the study aimed to answer the central question: “Can geographical possibilism demonstrate the importance of geography in geopolitics?”, where the analysis of the solar storm’s events and its main technological and educational consequences led to the conclusion that geography does indeed impact geopolitics, and human action also influences how geography affects Humanity.